Discretionary Policy (Freies Ermessen) of State Administrative Bodies or Officials in Government Administrative Law - Abdul Latif; Hery Chariansyah (International Journal Labs, 2024)
The aim is to examine and analyze how state government administrative agencies or officials carry out actions that are in accordance or not in accordance with the Ermessen freies legal conception itself which is known in scientific literature, especially state administrative law. In this case, the term